2019
DOI: 10.3389/fpsyg.2019.00507
|View full text |Cite
|
Sign up to set email alerts
|

Pathways Into Psychosocial Adjustment in Children: Modeling the Effects of Trait Emotional Intelligence, Social-Emotional Problems, and Gender

Abstract: Trait Emotional intelligence (Trait EI) can be understood as a personality trait related to individual differences in recognition, processing, and the regulation of emotionally charged information. Trait EI has been considered a variable of great importance in determining psychosocial adjustment. However, most research on Trait EI has focused on adult and adolescent populations, while very few studies have explored its influence on children. The aim of this study was to analyze possible pathways into psychosoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 71 publications
(102 reference statements)
1
38
0
1
Order By: Relevance
“…In general, scientific literature shows that academic achievement is related to self-concept (Susperreguy et al, 2018;Wolff et al, 2018;Sewasew and Schroeders, 2019), personality (Perret et al, 2019;Smith-Woolley et al, 2019), and EI (Corcoran et al, 2018;Deighton et al, 2019;Piqueras et al, 2019). Also, that within these construct, academic self-concept (Ferla et al, 2009;Guay et al, 2010;Chen et al, 2013;Marsh et al, 2014), intellect/imagination (Poropat, 2009;Smith-Woolley et al, 2019), and adaptability (MacCann et al, 2011;Szczygieł and Mikolajczak, 2017) correlate significantly with academic achievement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, scientific literature shows that academic achievement is related to self-concept (Susperreguy et al, 2018;Wolff et al, 2018;Sewasew and Schroeders, 2019), personality (Perret et al, 2019;Smith-Woolley et al, 2019), and EI (Corcoran et al, 2018;Deighton et al, 2019;Piqueras et al, 2019). Also, that within these construct, academic self-concept (Ferla et al, 2009;Guay et al, 2010;Chen et al, 2013;Marsh et al, 2014), intellect/imagination (Poropat, 2009;Smith-Woolley et al, 2019), and adaptability (MacCann et al, 2011;Szczygieł and Mikolajczak, 2017) correlate significantly with academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the scientific literature has shown that many studies have analyzed the relationship between academic achievement and different psychological constructs such as self-concept (Susperreguy et al, 2018;Wolff et al, 2018;Sewasew and Schroeders, 2019), personality (Janošević and Petrović, 2019;Perret et al, 2019;Smith-Woolley et al, 2019), and emotional intelligence (Corcoran et al, 2018;Deighton et al, 2019;Piqueras et al, 2019). In this work, these psychological constructs are analyzed together with primary school children by gender and cultural group.…”
Section: Introductionmentioning
confidence: 99%
“…Esta se ha conceptualizado y operacionalizado de dos formas distintas que han derivado en dos constructos complementarios: la IE como capacidad [ability] y la IE como rasgo [trait]. Si bien ambos constructos han mostrado asociaciones positivas con diversos indicadores de salud (Fernández-Berrocal y Extremera, 2016), la evidencia disponible indica que es la conceptualización de la IE rasgo la que cuenta con mayor evidencia de constituir un factor personal promotor de salud en niños, jóvenes y adultos (Petrides et al, 2017;Piqueras et al, 2019;Sarrionandia y Mikolajczak, 2019). El metaanálisis de Schutte et al(2007) confirmó que hay una asociación positiva entre IE y una mejor salud, mientras el metaanálisis acumulativo posterior de Martins et al (2010) ratificó esta conclusión haciéndola extensiva no sólo a salud mental sino también a salud psicosomática y física.…”
Section: Abstract: Emotions Emotional Health Health Education Health unclassified
“…Previous research has shown the negative consequences that social anxiety has for the life of an adolescent; for example, low acceptance among peers [17,18], a negative perception of the adolescent about himself/herself [19,20], and his/her social skills [21,22]. These consequences, in turn, involve risk factors for adolescent victimization in the school context [23,24].…”
Section: Introductionmentioning
confidence: 99%